2020
DOI: 10.1186/s12889-020-09277-1
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods research on satisfaction with basic medical insurance for urban and rural residents in China

Abstract: Background: There have been few studies on satisfaction with integrated basic medical insurance for urban and rural residents (URRBMI), and satisfaction with URRBMI is not very high because of the complexity of its policies and differences among the insured. The aim of the present study was to explore the factors that influence satisfaction with URRBMI in China and to provide scientific suggestions to the government for how to effectively manage and improve the policy. Methods: An explanatory sequential design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Although different variables, participants, and models were used by prior health insurance studies [20,22] as compared with our analysis, similar conclusions were drawn in terms of key factors influencing patient satisfaction, such as reimbursement ratio, the scope of healthcare services, and technologies listed in the insurance catalog. On the other hand, we identified several new findings that had not been reported by prior research.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Although different variables, participants, and models were used by prior health insurance studies [20,22] as compared with our analysis, similar conclusions were drawn in terms of key factors influencing patient satisfaction, such as reimbursement ratio, the scope of healthcare services, and technologies listed in the insurance catalog. On the other hand, we identified several new findings that had not been reported by prior research.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies [68][69][70] also proved that increase in patient satisfaction could have a positive impact on patients' trust. Another SEM research on URRBMI enrollees suggested that the perception of policy quality was a decisive factor in the perceived quality of URRBMI [20]. Given our results that patients' awareness of their insurance policies was very limited, it seemed to be a little bit difficult for patients to make a non-biased assessment of the policy quality.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations